New species of Oideterus Thomson (Coleoptera, Cerambycidae, Prioninae, Anacolini) and notes on O. lobicollis - Galileo, Maria Helena M.; Santos-Silva, Antonio (Zootaxa, 2015)
Oideterus inaequalis sp. nov. is described from Ecuador and compared with the holotype of O. lobicollis. The latter is excluded from the fauna of Ecuador. A key to known females of Oideterus is provided.